The role of celebrity endorsers, social media campaigns, and co-branding in shaping brand image: a case study of Es Teh Indonesia - Fataras Larasti; Susi Evanita (Marketing Management Studies, 2023)
This research purposes to analyze "The Effect of Celebrity Endorser, Social Media Marketing, and Co-Branding on The Brand Image of Es Teh Indonesia in Padang City". The population of this research is the people of Padang City who already know the brand of Es Teh Indonesia drink. This study used samples taken using the technique of purposive sampling with a sample of 170 people in 2023. This research was analyzed using SPSS version 25. With the following research results: (1) Celebrity endorser hasn’t significant effect on the brand image. (2) Social media marketing has positive and significant effect on the brand image. (3) Co-Branding has positive and significant effect on the brand image.